Comparative Study of Mechanical Properties of Concrete Using Marble Dust as Partial Cement Replacement and Addition of Polypropylene Fiber (International Journal of Innovative Research in Engineering & Management, 2022)
Ordinary Portland cement (OPC) is used as  the primary binder to produce concrete. The amount of the  CO₂ released during the manufacture of OPC is in the order  of one ton for every ton of OPC produced. Attempts made  to reduce the use of OPC in concrete are receiving much  attention due to environment related issues. In the present  study marble dust is used as a partial replacement for  cement. It has been estimated that several million tons of  Marble Dust are produced worldwide from extracting to  finishing process. Hence its utilization has become an  important alternative material because of its cement like  properties. Marble dust is also easily available at very less  cost. Concrete is characterized by quasi-brittle failure i.e;  once failure is initiated; nearly complete loss of loading  capacity takes place. By addition of randomly distributed  fibers in the concrete matrix concrete can be modified to  perform in a more ductile manner which prevent and  control initiation, propagation and coalescence of cracks. The fibers prevent surface cracking through bridging action  leading to an increased resistance of the concrete. This  paper presents results of an experimental program to  determine mechanical properties of concrete as cement is  replaced with marble dust with known percentages (0%, 5%, 10%, 15%) [5] [6] for the grade of M30 and addition of polypropylene fibers of different percentage (0%, 0.5%,  1%, and 1.5%). The concrete test samples were submitted to  compressive strength tests after 7 and 28 days of moist  curing, as well as flexure and splitting tensile strength tests. Overall Strength of Concrete (Compressive, Tensile &  Flexure) showed a reasonable increase upto a limit of 10%  for Marble Dust and 0.5% for PP Fibers [1].
Keywords: Compressive strength; Concrete; Flexural strength; Marble dust; Ordinary Portland cement; Polypropylene Fiber; Split tensile strength etc